A Real-Time Recombinase Polymerase Amplification Method for Rapid Detection of Vibrio vulnificus in Seafood - Yang, Xiaohan; Zhang, Xue; Wang, Yu; Shen, Hui; Jiang, Ge; Dong, Jingquan; Zhao, Panpan; Gao, Song (Frontiers in Microbiology, 2020)
As an important foodborne pathogen, Vibrio vulnificus gives a significant threat to food safety and public health. Rapid and accurate detection methods for V. vulnificus is required to control its spreading. The conventional detection methods are time-consuming and labor intensive, while the polymerase chain reaction (PCR)- and quantitative PCR (qPCR)-based methods are limited because of their dependence on laboratory equipment. Nucleic acid isothermal amplification technologies have been applied to develop simpler assays. In this study, a rapid detection method based on real-time recombinase polymerase amplification (RPA) targeting the extracellular metalloprotease (empV) gene of V. vulnificus has been established. The method finished the detection in 2-14 min at 39°C with good specificity. The limit of detection was 17 gene copies or 1 colony-forming unit (CFU) per reaction, or 1 CFU/10 g of spiked food with enrichment. In a clinical sample detection test, the results of real-time RPA were 100% consistent with bioassay and qPCR. Moreover, the method could resist the effect of food matrix and could tolerate crude templates. The real-time RPA method established in this study is rapid and simple, and has the potential to be widely applied for V. vulnificus detection in food safety control.